Multimodality and audiovisual translation: Subtitling Humor - Burczynska, Paulina (Lap Lambert, 2012)
Multimodality is an increasingly important area in applied linguistics and has begun to play a pivotal role in the act of communication. With the expansion of digital technology, the multimodal approach has also been applied to audiovisual translations with a special emphasis on subtitles. This study was designed to investigate the interplay between verbal and multimodal modes, i.e., semiotic, visual, acoustic, and kinetic, and to determine to what extent this interaction affects film subtitles. It is thus highly significant to assess when it is justifiable for a translator to obviate the original soundtrack in film subtitles when the same message is conveyed with the help of semiotic and multimodal modes other than language. The study also examines the influence of multimodal modes on humor translation and their impact on the humorous effect in a film. To investigate this issue selected scenes of the British sitcom ‘Fawlty Towers’ will be analyzed with its Polish subtitles. The thesis is a cross-linguistic, multimodal study that can be considered as the next step in the evolution of subtitles and is aimed at all of those who want to delve into the world of audiovisual translation